2020
DOI: 10.1101/2020.09.01.276097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electric Egg-Laying: Effect of Electric Field in a Microchannel onC. elegansEgg-Laying Behavior

Abstract: In this paper, the novel effect of electric field (EF) on adult C. elegans egg-laying in a microchannel is discovered and correlated with neural and muscular activities. The quantitative effects of worm aging and EF strength, direction, and exposure duration on egg-laying is studied phenotypically using egg-count, body length, head movement, and transient neuronal activity readouts. Electric egg-laying rate increases significantly when worms face the anode and the response is EF-dependent, i.e. stronger (6V/cm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The decrease in worms’ length might also be accompanied by possible changes in the worms’ muscle integrity. In our single-worm egg-laying experiments 28 , we showed that, during EF stimulations, worms contract their bodies in a consistent manner to release eggs. Body shortening was quantified in Figure 4E during the anodal pulses in the multi-worm device for the control and 100mM glucose-fed worms.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The decrease in worms’ length might also be accompanied by possible changes in the worms’ muscle integrity. In our single-worm egg-laying experiments 28 , we showed that, during EF stimulations, worms contract their bodies in a consistent manner to release eggs. Body shortening was quantified in Figure 4E during the anodal pulses in the multi-worm device for the control and 100mM glucose-fed worms.…”
Section: Resultsmentioning
confidence: 65%
“…Prior to EF stimulation, a 60 s acclimation period was used during which the flow was stopped by maintaining the inlet and outlet tubes at the same height level. Our previous experiments showed that the anode-facing worms could deposit significantly more eggs 27,35 , highlighting that the worm loading orientation with respect to the EF direction could affect our results. To maintain an equal exposure condition among randomly oriented worms in our device (as shown in Figure 2A), we adopted a new EF stimulation technique in which a series of 5s anodal and 5s cathodal pulses, separated by 25s acclimation periods, was applied for 10 min (Figure 2B).…”
Section: Methodsmentioning
confidence: 77%
See 3 more Smart Citations